DESAIN VISUAL BRANDING GITAR TERATE MUSIK MANCASAN BAKI SUKOHARJO - Itoh Yosie Prayogo; Evelyne Henny Lukitasari; Arif Yulianto (Akademi Seni dan Desain Indonesia Surakarta, 2024)
Along with the times, there are also many business opportunities to develop. In the Mancasan area, Baki Sukoharjo is famous for Kampung Gitar. Guitar is a musical instrument made of wood and plywood, Guitar is the most common musical instrument found and played by many people. Local Guitar Products from Mancasan Baki Sukoharjo are not only bought by lovers and stringed music players from Indonesia, original guitars of local craftsmen have managed to attract the attention of the international market. One of them is the Mancasan Baki Sukoharjo Music Terate Guitar craftsman entrepreneur, always maintaining its quality, namely wood and plywood raw materials and always innovating following the development of guitar variant models. And to maintain the Mancasan Baki Sukoharjo Music Terate Guitar product, namely for the purpose of designing this Final Project to produce Visual Branding of the Mancasan Baki Sukoharjo Music Terate Guitar which is applied to logos, t-shirts, roll banners, posters, stickers, hats and guitars. The design method includes 7 stages. Ideas, surveys, briefs, brain storming, creative briefs, design and evaluation. The Visual Design Design Branding of Mancasan Baki Sukoharjo Music Terate Guitar was carried out with a concept shown to strengthen the image of the Mancasan Baki Sukoharjo Music Terate Guitar and convey the superior variant of the Mancasan Baki Sukoharjo Music Terate Guitar. The final result of this final project work is used to promote local products with services from the Mancasan Baki Sukoharjo Music Terate Guitar. Keywords: Guitar Terate Music. Visual Branding Design. Mancasan Baki Sukoharjo